Subtle Implicit Language Facts Emerge from the Functions of Constructions - Goldberg, Adele E. (Frontiers in Psychology, 2016)
Much has been written about the unlikelihood of innate, syntax-specific, universal knowledge of language (Universal Grammar) on the grounds that it is biologically implausible, unresponsive to cross-linguistic facts, theoretically inelegant, and implausible and unnecessary from the perspective of language acquisition. While relevant, much of this discussion fails to address the sorts of facts that generative linguists often take as evidence in favor of the Universal Grammar Hypothesis: subtle, intricate, knowledge about language that speakers implicitly know without being taught. This paper revisits a few often-cited such cases and argues that, although the facts are sometimes even more complex and subtle than is generally appreciated, appeals to Universal Grammar fail to explain the phenomena. Instead, such facts are strongly motivated by the functions of the constructions involved. The following specific cases are discussed: a) the distribution and interpretation of anaphoric one, b) constraints on long-distance dependencies, c) subject-auxiliary inversion, and d) cross-linguistic linking generalizations between semantics and syntax.